O-217 Air quality and health co-benefits of climate change mitigation and adaptation actions by 2030: an interdisciplinary modeling study in Ahmedabad, India. (14th March 2023) - Dutta, Priya; Pingle, Shyam; Madan, Prima; Mukerjee, Polash; Limaye, Vijay S; Mavalankar, Dileep; Knowlton, Kim
Abstract : Introduction: An unprecedented urbanization and population encroachment in Indian cities are making it's urban population more vulnerable to climate change and air pollution effects. Using an interdisciplinary modelling approach, our team has estimated the health co-benefits of mitigation and adaptation policies in Ahmedabad, India, through collaboration among the Indian Institute of Tropical Meteorology (IITM), Gujarat Energy Research & Management Institute (GERMI), Indian Institute of Public Health Gandhinagar (IIPH-G), and the Natural Resources Defense Council (NRDC) and an applied research project funded by the Wellcome Trust's Our Planet, Our Health Program. Method: We selected Ahmedabad city as it's experiencing extreme heat wave events in summer. The project aim was to estimate the local health benefits of actions to reduce air pollution emissions and adapt to climate change in Ahmedabad, India, by the year 2030 using open-access BenMAP modelling software. We compared the relative health impacts of putting two climate strategies in place by 2030: more reliance on cleaner, renewable energy sources instead of coal; and expanding cool roof installation area across the city. Results: Our results yielded local, city-specific insights on climate change and energy demand, as well as air quality and health. On air quality and health, annual average fine particle air pollution (PM2.5) would climb to 75.18 ug/m3 by 2030 under BAU. But with mitigation and adaptation strategies put in place, air quality would improve; lower PM2.5 concentrations (70.95 ug/m3) would mean 1, 414 fewer all-cause deaths across the city by 2030. Furthermore, thousands more premature deaths could be avoided by meeting air quality standards: under the National Clean Air Program (NCAP), 6, 510 annually; under the National Ambient Air Quality Standards (NAAQS), 9, 047 annually; and under the World Health Organization (WHO) air quality guidelines, 17, 369 annually. Moreover, one sees how climate adaptations can mean saving energy, and climate mitigation can mean saving lives.